PERKEMBANGAN MOTORIK HALUS ANAK DI KOMUNITAS “X” - Shinta Trisnanda Dewi; Risa Dwi Meilani; Novia Novitasari; Ima Fitri Sholichah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2025)
Background: Fine motor skills play an important role in child development. Lack of parental stimuli and the influence of the social environment during the child's golden age can be factors of developmental delays. Community as a part of society can play a role in fulfilling these needs. Objective: This study aims to explore children's fine motor skills development in the "X" community after implementing playdough intervention. Method: This study uses a qualitative descriptive method with the subjects being five children from the "X" community, aged 6-10 years, and having poor fine motor skills selected through purposive sampling techniques. Data was collected through observation during the intervention and the results of the Frostigg test. The data analysis technique used is a qualitative descriptive method. Result: The results of this study indicate that children's fine motor skills increased after the study using playdough.. Conclusion: Playdough has been proven to help develop children's fine motor skills in the "X" community. Playdough can be used as an easy and inexpensive play media solution to improve children's fine motor skills.